(untitled) (CIPEEX, 2026)
Introduction: Genetic mapping for breast and ovarian cancer has gained prominence as a preventive strategy, especially in contexts with personal or family history of the disease. However, factors such as education level and previous experience with cancer may influence its acceptance. Objective: To analyze the perception of the population of Goiás regarding genetic mapping for breast and/or ovarian cancer, also investigating the relationship between sociodemographic characteristics and participants’ willingness to undergo the test. Methodology: This is a cross-sectional study with 239 adults residing in Goiás, recruited through digital platforms. Participants answered an electronic questionnaire specifically designed for this population, based on a literature review on the topic. Statistical analysis was performed using IBM SPSS Statistics (v.17.0), applying Pearson’s chi-square test and binary logistic regression, with a significance level set at 5%. Results: Among women, education beyond 12 years was associated with greater willingness to undergo genetic testing. Income, age, marital status, and skin color showed no significant associations. Conclusion: It is essential to invest in educational strategies targeting populations with lower education levels, in addition to expanding dialogue on the subject in primary care. Qualitative studies may further deepen the understanding of these decisions.